Electricity economics for ex‐ante double‐sided auction mechanism in restructured power market - Aruna Kanagaraj; Kumudini Devi Raguru Pandu (Energy Conversion and Economics, 2022)
Abstract Auction mechanism analysis provides favourable economic outcomes for key stakeholders involved in the restructured power market. Real power pricing based on locational marginal pricing has been implemented in the electricity market worldwide. In this study, the optimal power flow is considered to minimise the operating cost of the active power generation in the ex‐ante energy market and an augmented optimal power flow in the ex‐ante reserve market. The double‐sided auction mechanism has better control over the energy and reserve markets, enhancing social welfare in the restructured power markets. Single‐ and double‐sided auction mechanisms are considered to analyse the allocation and pricing economics in the ex‐ante day‐ahead energy and ex‐ante day‐ahead reserve markets. Locational marginal pricing is calculated and analysed for both the on‐and off‐peak demand periods. The proposed auction model was validated using an IEEE 30‐bus power system. The benefits of the double‐sided auction are assessed from technical and economic perspectives.